SELETIVIDADE DE ARMADILHAS MALAISE PARA COLETA DE INSETOS NO ECÓTONO CERRADO-PANTANAL SUL-MATO-GROSSENSE - SIMPLICIO, Viviane dos Santos; SIMPLICIO, Vitor Hugo dos Santos; ESPIRITO SANTO, Fabíola do; ABOT, Alfredo Raul (ANAIS DO ENIC, 2018)
-